(untitled) (Pedagogical Horizons, 2021)
On the basis of the article “Nebeneinander ohne Konflikte. Die multiprofessionelle Struktur interreligiöser Lehrgemeinschaften” (“Side by side without conflicts. The multi-professional structure of interreligious teachers’ cooperation”), this article reconstructs the professional types of religion teachers that manifest themselves in the interview on Christian-Islamic team teaching. In the group discussion between the Catholic and the Islamic religion teacher and the research team, divergent orientation schemata concerning proper religious education can be reconstructed on a subject-specific as well as a didactic level. This points to conflicting orientation frames concerning the question of how religious education ought to profit children, society and the religious community. In a relational analysis, these orientation frames are condensed into two opposing professional types, a problem-oriented/emancipatory one and a content-oriented one, which are integrated into the discourse about religious learning in our modern times and pluralistic society. In terms of religious education, the first type appertains to the basic idea of correlation didactics, whereas the second is related to a catechetical/material-kerygmatic concept. The difference in the orientation frames significantly complicates (inter-)professional cooperation. Finally, the article discusses the consequences of these findings for the discourse on religious education and the future training of religion teachers.